Home‐based HPV self‐sampling improves participation by never‐screened and under‐screened women: Results from a large randomized trial (iPap) in Australia. Issue 2 (10th March 2016) - Sultana, Farhana; English, Dallas R.; Simpson, Julie A.; Drennan, Kelly T.; Mullins, Robyn; Brotherton, Julia M.L.; Wrede, C. David; Heley, Stella; Saville, Marion; Gertig, Dorota M.
Abstract : We conducted a randomized controlled trial to determine whether HPV self‐sampling increases participation in cervical screening by never‐ and under‐screened (not screened in past 5 years) women when compared with a reminder letter for a Pap test. Never‐ or under‐screened Victorian women aged 30–69 years, not pregnant and with no prior hysterectomy were eligible. Within each stratum (never‐screened and under‐screened), we randomly allocated 7, 140 women to self‐sampling and 1, 020 to Pap test reminders. The self‐sampling kit comprised a nylon tipped flocked swab enclosed in a dry plastic tube. The primary outcome was participation, as indicated by returning a swab or undergoing a Pap test; the secondary outcome, for women in the self‐sampling arm with a positive HPV test, was undergoing appropriate clinical investigation. The Roche Cobas® 4800 test was used to measure presence of HPV DNA. Participation was higher for the self‐sampling arm: 20.3 versus 6.0% for never‐screened women (absolute difference 14.4%, 95% CI: 12.6–16.1%, p < 0.001) and 11.5 versus 6.4% for under‐screened women (difference 5.1%, 95% CI: 3.4–6.8%, p < 0.001). Of the 1, 649 women who returned a swab, 45 (2.7%) were positive for HPV16/18 and 95 (5.8%) were positive for other high‐risk HPV types. Within 6 months, 28 (62.2%) women positive for HPV16/18 had colposcopy as recommended and nine (20%) had cytology only. Of women positive for other high‐risk HPV types, 78 (82.1%) had a Pap test as recommended. HPV self‐sampling improves participation in cervical screening for never‐ and under‐screened women and most women with HPV detected have appropriate clinical investigation. Abstract : What's new? For women who have not had a recent Pap test, self‐sampling for human papillomavirus (HPV) can potentially improve participation in cervical cancer screening. The present study emphasizes the degree to which home‐based HPV self‐sampling can increase participation, particularly among women never previously screened. More than three times as many never‐screened women participated in self‐sampling compared to the number who underwent Pap testing as a result of traditional invitation or reminder strategies. Among never‐screened and under‐screened women who tested positive for high‐risk HPV types via self‐sampling, more than four‐fifths subsequently underwent Pap testing or appropriate clinical investigation.